EFFECTIVENESS OF GROUP GUIDANCE SERVICES USING SELF-REGULATED LEARNING TECHNIQUES TO REDUCE ACADEMIC BURNOUT IN CLASS X STUDENTS OF YPK MEDAN VOCATIONAL SCHOOL - Deliska Putri, Girna; Hasibuan, M. Fauzi (BRIGHT VISION Journal of Language and Education, 2023)
This research aims to determine the picture of academic burnout on YPK Medan Vocational School Students. The purpose of this research is too: describe the difference in scores in reducing academic burnout in students experimental group before and after being given service treatment group guidance using self-regulated learning techniques. Whereas control group before and after being given treatment with services group counseling. This research is a quantitative type of research experimental research. The object of this research is class X OTKP SMK YPK Medan. The data collection technique in this research used a questionnaire to students who experience academic burnout. The results of this research show that students who experience academic burnout are seen from several indicators including physical fatigue, emotional exhaustion, feelings of low self-esteem, depersonalization, and decreased academic confidence. Analysis test results using the Wilcoxon Signed Ranks Test and the Kolmogorov Smirnov analysis test Teo Independent Samples. Thus, based on the research results carried out include: (1) there is a significant difference in academic burnout students in the experimental group before (pretest) and after (posttest) with group guidance services using self-regulated learning techniques. (2) there is a significant difference in students academic burnout in the control group before (pretest) and after (posttest) with group guidance services. (3) there are significant differences in student academic burnout between groups experimental and control groups given treatment.